2018
DOI: 10.1002/ange.201807317
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the Same Reaction Monitored over Nine Orders of Magnitude in Concentration: When Are Unique Subensemble and Single‐Turnover Reactivity Displayed?

Abstract: Essentially no information is knowna bout the behavior of individual molecular catalysts under reaction conditions.T his is ar esult of the averaging inherent to traditional analytical techniques.H erein, ac ombined fluorescence microscopyand 1 HNMR spectroscopystudy reveals that unique (that is,non-ensemble averaged) distributions and timevariable kinetics from molecular ruthenium catalysts within growing polynorbornene occur and are detectable between 10 À9 m and 10 À6 m of substrate,s urprisingly just 1000-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Further expansion of these studies into polymer tethers for catalysts was suggested as a future opportunity for additional studies, and several of these works were performed to fill the gap in polymer initiation via catalysis. 26,[153][154][155][156]…”
Section: Catalytic Synthesismentioning
confidence: 99%
See 4 more Smart Citations
“…Further expansion of these studies into polymer tethers for catalysts was suggested as a future opportunity for additional studies, and several of these works were performed to fill the gap in polymer initiation via catalysis. 26,[153][154][155][156]…”
Section: Catalytic Synthesismentioning
confidence: 99%
“…219 The ability to image this reaction is attributed to rapid diffusion rates of norbornene monomer relative to the growing polymer chains, leading to a high resolution for spatial localization. 154,156,219,226 However, this technique relied on the ruthenium catalyst being in the active state, and the polymer could not be imaged otherwise. 219 These studies were eventually expanded to determine individual molecule kinetics of ruthenium catalyst-governed ROMP which varied from bulk concentration kinetics for the same reaction.…”
Section: Catalyzed Polymerizationsmentioning
confidence: 99%
See 3 more Smart Citations